Characterization and functional correlation of multiple imaging modalities with focal choroidal excavation. Issue 5 (May 2018) - Chen, Yun‐Chen; Chou, Yu‐Bai; Lin, Cheng‐Kuan; Tsai, Chia‐Chen; Hsu, Tsui‐Kang; Chang, Yu‐Fan; Chao, Hsiao‐Ming; Tung, Tao‐Hsin; Chen, Shih‐Jen; Liu, Jorn‐Hon
Abstract : Background: : To investigate the clinical manifestations and imaging features of near‐infrared autofluorescence (NIA), infrared reflectance (IR), fundus autofluorescence (FAF), indocyanine green angiography (ICGA) and fluorescein angiography (FAG) in the detection of patients with focal choroidal excavation (FCE) identified by cross‐sectional spectral‐domain optical coherence tomography (SD‐OCT). Methods: : This retrospective cross‐sectional study included 12 eyes of 10 Taiwanese patients with FCE diagnosed by SD‐OCT. The areas and depths of FCE in serial cross‐sectional and en‐face OCT were compared in different imaging modalities. NIA, IR, FAF, ICGA and FAG images were obtained. Best corrected visual acuity, subjective distortion area in the Amsler grid and history of maculopathies were also recorded. Results: : In areas where the choroid started to excavate as shown in SD‐OCT, hypo‐autofluorescence in NIA was noted. The area of hypo‐fluorescence in NIA of all the FCE lesions showed good correlation with the size. The area of FCE was associated with complications such as choroidal neovascularization and central serous chorioretinopathy ( p = 0.014, d.f = 1) and the volume (NIA area × Depth measured by SD‐OCT × 1/3) was associated with subjective distortion strongly ( p = 0.051, Spearman's correlation = 0.600). Conclusion: : Among all image modalities, NIA was the most sensitive tool in area measurement of FCE and peripheral lesion detection. Also, the volume of FCE was associated with subjective distortion and the area was related to complications. Recording the area and volume of FCE could play an important role in monitoring complications.